The Pathophysiological Link Between Reelin and Autism: Overview and New Insights - Scala, Marcello; Grasso, Eleonora A.; Di Cara, Giuseppe; Riva, Antonella; Striano, Pasquale; Verrotti, Alberto (Frontiers in Genetics, 2022)
Reelin is a secreted extracellular matrix protein playing pivotal roles in neuronal migration and cortical stratification during embryonal brain development. In the adult brain, its activity is crucial for synaptic plasticity, memory processing, and cognition. Genetic alterations in RELN have been variably reported as possible contributors to the pathogenesis of autism spectrum disorders (ASD). In particular, GCCs repeats in the 5’ UTR and single nucleotide polymorphysms (SNPs) in RELN have been suggested to affect brain development and predispose to autism. We reviewed pertinent literature on RELN expression and haplotypes transmission in children with ASD, critically analyzing available evidence in support of the pathophysiological association between Reelin deficiency and ASD.